2020
DOI: 10.33474/elementeris.v2i1.4903
|View full text |Cite
|
Sign up to set email alerts
|

Respon Siswa Terhadap Penggunaan Modul Tematik Dalam Meningkatkan Kemampuan Berpikir Kritis

Abstract: This research aimed to determine students' responses to the use of thematic modules based on the integration of Islam and science in improving critical thinking skills on energy themes and their changes in 3rd grade MI Salafiyah Kutukan Blora. The research method apply in this research is descriptive research. The Descriptive research used in this research is the survey. The research instrument used was a student response questionnaire. Analysis of student response questionnaires showed that 80,3% of students … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 1 publication
0
1
0
3
Order By: Relevance
“…This is inseparable from the use of joyful learning-based Integrated Science e-modules that run smoothly, making students more active and enjoyable. In line with Khairiyah & Faizah (2020), which states that the advantages of learning that emphasizes the critical thinking process are that students will have the ability to solve problems both in the classroom and in the classroom and in dealing with real problems experienced. Soenarno (2017) revealed that the use of active and enjoyable learning can make students more enthusiastic in following the learning so that learning achievements increase.…”
Section: Implementation Of E-module Integrated Science Based On Joyfu...mentioning
confidence: 96%
“…This is inseparable from the use of joyful learning-based Integrated Science e-modules that run smoothly, making students more active and enjoyable. In line with Khairiyah & Faizah (2020), which states that the advantages of learning that emphasizes the critical thinking process are that students will have the ability to solve problems both in the classroom and in the classroom and in dealing with real problems experienced. Soenarno (2017) revealed that the use of active and enjoyable learning can make students more enthusiastic in following the learning so that learning achievements increase.…”
Section: Implementation Of E-module Integrated Science Based On Joyfu...mentioning
confidence: 96%
“…Angket akan dianalisis dengan Setiap 1 jawaban "ya" dari tipe pertanyaan positif akan diberi skor dengan 1 poin dan setiap 1 jawaban "tidak" dari tipe pertanyaan negatif akan diberi skor dengan 1 poin. (Khairiyah & Faizah, 2020) Berdasarkan penggunaan fitur-fitur Web Quizlet pada setiap proses pembelajaran. Dapat diketahui bahwa koneksi internet sangatlah yang terpenting dalam proses pembelajaran Daring.…”
Section: Metode Penelitianunclassified
“…Untuk mewujudkan hakikat, fungsi, dan tujuan pendidikan tersebut maka perlu didukung dengan beberapa hal seperti kurikulum yang adaptif, pendidikan yang profesional, sarana prasarana yang memadai serta dukungan penuh dari pemerintah dan masyrakat. Selain itu pembelajaran juga dapat memanfaatkan modul untuk meningkatkan keterampilan berpikir kritis siswa (Khairiyah & Faizah, 2019) dan perlu di desain secara kreatif, menantang, dan memberikan ruang bagi siswa untuk berkreasi (Munir & Sholehah, 2019).…”
Section: Pendahuluanunclassified